Understand The Naktu In The Direction Of The Main Door Of The Suhunan Of The Kasepuhan Gelaralam Sundanese - Purba, Zixza Liana (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Kasepuhan Gelaralam is a new traditional village from the previous Kasepuhan Ciptagelar. Kasepuhan Gelaralam still upholds its rice culture. The village move, called ngalalakon, will take place in early 2022. In the tradition of building houses or Suhunan, they have a rule of using naktu (birthday) calculations to determine the direction the main door faces. The direction the door is facing aims to provide safety and keep away from disaster for the residents of Suhunan. The main door at Suhunan in Kasepuhan Gelaralam is the kitchen door because in the kitchen there is a core room called pangdaringan (rice storage place). It is believed that this room is where the Goddess of Rice resides. This article aims to determine whether there is an influence of naktu in accordance with Kasepuhan Gelaralam culture with naptu based on interviews and physical field data from the Kasepuhan Gelaralam community. This research is qualitative-inductive research using ethnographic strategies in data collection and analysis. The results of this research indicate that there is a misperception by the people of Kasepuhan Gelaralam regarding the naktu value of the Gelaralam calendar and the Javanese neptu, so that the direction facing the main door Suhunan in Kasepuhan Gelaralam is wrong. Therefore, the ngaruwat ritual is carried out overtime which aims to cleanse the entire village from danger and disaster. Keywords: Naktu, forward direction, main door, suhunan